Associações entre remuneração, motivação e desempenho individual - Oliveira Junior, Pedro Joaquim de (2020)
The purpose of this study was to evaluate the relationships that variable compensation has on motivation (intrinsic and extrinsic) and also the joint effect they have on individual employee performance. The study was classified as descriptive and, regarding the approach, framed as hypothetical-deductive, whose hypotheses were built through the literature. Through a survey applied to professionals working in goal-oriented departments, we have a quantitative study. Data collection was performed by sending the questionnaire by email to potential respondents, returning a sample with 122 respondents. For data analysis, a structural equation was constructed and the tests applied in SmartPLS. The results showed that the individual performance of the employee is positively affected by variable compensation and intrinsic motivation. Extrinsic motivation, in turn, has a minor influence on performance, tending to decrease it. When tested the influences of remuneration on both types of motivation, there was a negative aspect to intrinsic motivation and positive on extrinsic motivation. It seeks to contribute to goal setting in organizations and performance control through variable compensation, in order to clarify the relevant aspects of the factors that influence the execution of employees activities and the construction of motivation, intrinsic and extrinsic.